Oligodendrocyte precursor cells facilitate neuronal lysosome release - Fang, Lipao; Lin, Ching-Hsin; Medlej, Yasser; Zhao, Renping; Chang, Hsin-Fang; Guo, Qilin; Wu, Zhonghao; Su, Yixun; Zhao, Na; Gobbo, Davide; Wyatt, Amanda; Wahl, Vanessa; et al. (Nature Communications, 2025)
Oligodendrocyte precursor cells (OPCs) shape brain function through many non-canonical regulatory mechanisms beyond myelination. Here we show that OPCs form contacts with their processes on neuronal somata in a neuronal activity-dependent manner. These contacts facilitate exocytosis of neuronal lysosomes. A reduction in the number or branching of OPCs reduces these contacts, which is associated with lysosome accumulation and altered metabolism in neurons and more senescent neurons with age. A similar reduction in OPC branching and neuronal lysosome accumulation is seen in an early-stage mouse model of Alzheimer’s disease. Our findings have implications for the prevention of age-related pathologies and the treatment of neurodegenerative diseases.